Mesenteric vein thrombosis following laparoscopic appendectomy - Jamie Harris; Brian Blackwood; Srikumar Pillai; Bill Chiu (Elsevier, 2014)
Mesenteric vein thrombosis is an uncommon complication following laparoscopic surgery. A review of the literature has shown that there is a higher incidence of thrombosis following laparoscopic bariatric procedures, including the gastric sleeve procedure and roux-en-y gastric bypass surgery. Additionally, pylephlebitis, thrombosis of portal or mesenteric veins, has been described following perforated appendicitis. However no report has described mesenteric vein thrombosis following laparoscopy for nonperforated appendicitis in the pediatric population. The cause of this thrombosis is hypothesized to be secondary to venous stasis secondary to insufflation during laparoscopy.